Advances in Multi-Omics Approaches for Molecular Breeding of Black Rot Resistance in Brassica oleracea L. - Shaw, Ranjan K.; Shen, Yusen; Wang, Jiansheng; Sheng, Xiaoguang; Zhao, Zhenqing; Yu, Huifang; Gu, Honghui (Frontiers in Plant Science, 2021)
Brassica oleracea is one of the most important species of the Brassicaceae family encompassing several economically important vegetables produced and consumed worldwide. But its sustainability is challenged by a range of pathogens, among which black rot, caused by Xanthomonas campestris pv. Campestris (Xcc) is the most serious and destructive seed borne bacterial disease, causing huge yield losses. Host-plant resistance could act as the most effective and efficient solution to curb black rot disease for sustainable production. Recently, the ‘omics’ technologies have emerged as promising tools to understand the host-pathogen interactions, thereby gaining a deeper insight into the resistance mechanisms. In this review, we have summarized the recent achievements made in the omics technologies to tackle the black rot challenge in B. oleracea. With an integrated approach of the omics technologies such as genomics, proteomics, transcriptomics and metabolomics, it would allow better understanding of the complex molecular mechanisms underlying black rot resistance. Genomic studies revealed that the black rot resistance is a complex trait and is mostly controlled by QTLs with minor effects except few major effect QTLs. Transcriptomic analysis divulged the genes related to photosynthesis, glucosinolate biosynthesis and catabolism, phenylpropanoid biosynthesis pathway, ROS scavenging, calcium signalling, hormonal synthesis and signalling pathway are being differentially expressed upon Xcc infection. Comparative proteomic analysis in relation to susceptible and/or resistant interactions with Xcc identified the involvement of proteins related to photosynthesis, protein biosynthesis, processing and degradation, energy metabolism, innate immunity, redox homeostasis, and defense response and signalling pathways in Xcc-Brassica interaction. Metabolomic studies suggested that glucosinolates especially aliphatic and indolic GSLs, and defensive metabolites synthesized by JA-mediated phenylpropanoid biosynthetic pathway are involved in disease resistance mechanisms against Xcc. So, the bonhomie between multi-omics technologies and plant breeding is going to trigger major breakthroughs in the field of crop improvement by developing superior cultivars. In this review, we have discussed the challenges, future prospects and the way forward in the application of omics technologies to accelerate the breeding of B. oleracea for disease resistance. A deeper insight of the current knowledge on omics can offer promising results in the breeding of high-quality disease-resistant crops.